A Critique and Review on the Book Inclusive Growth in Iran’s Provinces: Policies and Indicators - Amir Hossein Mozayani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Achieving continuous economic growth has been and is one of the focal points in policy-making. This issue is mostly studied using economic growth models and approaches. One of the newest approaches to economic growth is pro-poor growth and subsequently the inclusive growth. These two approaches were offered when it was observed that poor people do not enjoy the benefits of economic growth comparing to other sections of society. One of the books published in this field is the book "Inclusive Growth in the Provinces of Iran: Policies and Indicators", the review and critique of which is on the agenda of this article and meanwhile attempts are made to provide suggestions for improving the content of the book in future editions. The findings of the book indicate that economic growth in Iran has been low in recent years and at the same time labor force participation has played an effective and significant role in the overall growth in the provinces. However, government policies that could have played an effective role in reducing poverty and inequality in the provinces have not been very successful in practice. In conclusion, it seems that moving toward inclusive growth requires the design and implementation of a coherent policy package from different dimensions.